Exposure to models' positive facial expressions whilst eating a raw vegetable increases children's acceptance and consumption of the modelled vegetable. (1st January 2022) - Edwards, Katie L.; Thomas, Jason M.; Higgs, Suzanne; Blissett, Jacqueline
Abstract: Research has shown that seeing positive facial expressions (FEs) towards food increased children's desire to eat foods rated as disliked. However, the effect of adults' positive FEs whilst eating a raw vegetable on children's acceptance and intake of nutritious foods that are less preferred (e.g., vegetables) remains to be established. This study aimed to examine the effect of models' FEs eating raw broccoli on children's acceptance and intake of raw broccoli. 111 children aged 4–6 years (64 male, 47 female) were randomised to watch a video of unfamiliar adult models eating raw broccoli with a positive or neutral facial expression (FE), or a non-food control video. Children's acceptance and intake of raw broccoli was assessed. Data about parent and child characteristics was provided by parents. There was a main effect of FE type on children's frequency of tastes ( p  = .03) and intake of broccoli ( p  = .02). Children who were exposed to models eating broccoli with positive FEs had greater frequency of tastes ( p  = .04) and intake of broccoli ( p  = .03), than children in the control condition, but not compared to children in the neutral FE condition ( p  > .05). There was no effect of positive FEs on children's willingness to try broccoli ( p  > .05). These findings suggest that observing others enjoy a commonly disliked vegetable can encourage children's tastes and intake of the vegetable. Thus, exposing children to others enjoying vegetables could be a useful strategy for encouraging healthier eating in children. Further work is needed to determine whether a single exposure is sufficient and whether these effects are sustained over time.